Studies on polynuclear furoquinones. Part 1: Synthesis of tri- and tetra-cyclic furoquinones simulating BCD/ABCD ring system of furoquinone diterpenoids - Shaik, Faruk Hasan; Kar, Gandhi Kumar (Beilstein Journal of Organic Chemistry, 2009)
Synthesis of phenanthro[1,2-b]furan-10,11-dione, the core nucleus present in Tanshinone-I is described in 8–10 steps starting from 2-bromo-3,4-dihydro-1-naphthaldehyde. The bromoaldehyde was converted to methyl 2-(2-bromo-1-naphthyl)acetate or 2-(2-bromo-1-naphthyl)acetonitrile following the protocol of functional group transformations. Subsequent Suzuki coupling of this ester/nitrile derivative with furan-2-boronic acid produced [2-(2-furyl)-1-naphthyl]acetic ester/nitrile which on hydrolysis furnished the corresponding acid derivative. Cyclization of the acid followed by oxidation of the phenol, with Fremy’s salt, produced the tetra-cyclic furoquinone, phenanthro[1,2-b]furan-10,11-dione. This method has also been extended for the synthesis of the tricyclic furoquinone, naphtho[1,2-b]furan-4,5-dione.
Keywords: Fremy’s salt oxidation; furonaphthoquinone; furophenanthraquinone; Suzuki reaction